Viabilidade tecnológica da triploidia em Anomalocardia brasiliana (Bivalvia: Veneridae) em escala laboratorial - LAVANDER, Henrique David (2018)
Polyploidy, through chromosome manipulation, is one of the most important tools to improve zootechnical performance in poultry farming and is responsible for the greatest advances in this sector. Cytogenetic studies may provide essential information for chromosome manipulation directed to the production of polyploid organisms. In the present study, the post-fertilization moments in which the polar bodies are expelled were identified, as well as the most frequent number of chromosomes in Anomalocardia brasiliana. Induction to triploidy by chemical and physical induction was evaluated using the inducers Cytochalasin B (CB) and 6-Dimethylaminopurine (6-DMAP), as well as by cold thermal shock and hyposmotic shock, respectively. The specimens were captured on the north coast of Pernambuco, northeast, on the beach of Mangue Seco, and south of Espírito Santo, southeast region, on the beach of Piúma, Brazil. The gametes were obtained by induction, oocyte solution samples were taken before and after fertilizations every two minutes. The material was fixed in Carnoy stained in DAPI (4',6-diamidino-2-phenyloindole) at 2μg / mL, and photographed under an epifluorescence microscope. Induction to triploidia by CB was performed at 1 mg. L-1, whereas induction by 6-DMAP was done at 450 μmol.L-1. The inductions by cold thermal shock were performed at 2, 5 and 7°C, and by hyposmotic shock performed at 12‰ of salinity. A total of 19 bivalents were observed in 50 oocytes at the metaphase I stage. In 70% of the eggs, the first polar body was detected at ten minutes after fertilization, and in 62% of the eggs the second polar body was expelled at 16 minutes. These percentages were obtained at a mean temperature of 26°C and 35‰ of salinity. The chemical inductions to triploidia presented low larval survival after the first 24 hours, unlike the physical treatments, which obtained more than 90% survival. The results obtained in this research may support other studies involving genetic manipulation for the purpose of polyploidy in aquaculture.